Relationship between socio-economic and anthropometric status of young children in rural Bangladesh - Moniruzzaman, Syed (BRAC Research and Evaluation Division (RED), 2020)
This study investigates the interrelationship between socio-economic status and anthropometric measurements of young children in rural Bangladesh. A nutrition surveillance system programme (the NSP) was established in April 1990. This is a collaborative effort that involves international and indigenous non-governmental organisations (NGO) and the government of Bangladesh, and is co-ordinated by Helen Keller International and funded by the US Agency for International Development. Data were collected every two months by ten NGOs and the Bangladesh government from 26 sentinel points, corresponding to 20 subdistricts and 4 urban slums. In each round of data collection, 5000-6000 households are randomly selected, and anthropometric measurements are taken from 7,000-9,000 children between the ages of 6 and 59 months. Data for this study came from Mohanpur, Manda, Bhuapur and Dagonvhuiya subdistricts, the vital registration area of the NGOs ASA, Shwanirvar Bangladesh and VERC. Anthropometric and socio-economic data concerning 1562 children aged 6-59 months were collected. From these data, it was found that the proportion of malnourished children was very high, underweight 59%, and stunted 56%. Malnutrition of the child was related to low educational level of the mother and poor condition of housing. Poor housing may be regarded as a proxy for poor socio-economic conditions. The different characteristics of the socio-economic conditions of the household were closely related, and not easily separated in relation to malnutrition of the child. The conclusion of this study is that preventive efforts improving the socio-economic condition of families with children and the educational level of mothers may have profound effects on child health.